Radiological outcome in rheumatoid arthritis is predicted by presence of antibodies against cyclic citrullinated peptide before and at disease onset, and by IgA-RF at disease onset. Issue 4 (21st September 2005) - Berglin, E; Johansson, T; Sundin, U; Jidell, E; Wadell, G; Hallmans, G; Rantapää-Dahlqvist, S
Abstract : Objective: To evaluate the significance of antibodies against cyclic citrullinated peptide (anti-CCP) and rheumatoid factors (RFs), before the onset of rheumatoid arthritis and when presenting as early disease (baseline), for disease activity and progression. Methods: 93 of a cohort of 138 patients with early rheumatoid arthritis (<12 months of symptoms) had donated blood before symptoms of rheumatoid arthritis (defined as pre-patients) and were identified from among blood donors within the Medical Biobank of northern Sweden. Disease activity (erythrocyte sedimentation rate (ESR), C reactive protein, joint score, global visual analogue scale) and radiological destruction in hands and feet (Larsen score) were assessed at baseline and after two years. Anti-CCP antibodies and RFs were analysed using enzyme immunoassays. HLA shared epitope (SE) alleles (DRB1*0401/0404) were identified. Results: Patients with anti-CCP antibodies before disease onset had significantly higher Larsen score at baseline and after two years. In multiple regression analyses baseline values of anti-CCP/IgA-RF/IgG-RF/IgM-RF, swollen joint count, and Larsen score significantly predicted radiological outcome at two years. In logistic regression analyses, baseline values of anti-CCP antibodies/IgA-RF, therapeutic response at six months, and swollen joint count/ESR significantly predicted radiological progression after two years. The baseline titre of anti-CCP antibodies was higher in patients with radiological progression and decreased significantly in those with response to therapy. SE allele carriage was associated with a positive test for anti-CCP antibodies in pre-patients and in early rheumatoid arthritis. Conclusions: Presence of anti-CCP antibodies before disease onset is associated with more severe radiological damage. The titre of anti-CCP antibodies is related to disease severity.